Biodiesel production from solid coconut waste - Sulaiman, Sarina (2013)
Raw material from waste sources such as used bleaching earth, spent coffee ground, waste cooking oil, animal fat and sludge are increasingly being exploited in biodiesel production because of the cost and environmental considerations. Obtaining cheaper raw materials are one of the continuous targets of many biodiesel producing facilities since 70 to 95 % of the production costs are attributed to raw materials. In Malaysia, about 78 thousand metric tons of coconut wastes were produced in 2010. Typically coconut waste still contain up to 24 wt % extractable oil content and is suitable for biodiesel production. It is estimated that 178 thousand tonne of oil could be produced from solid coconut waste and about 167 thousand tonne of biodiesel. In this work, solid coconut waste was evaluated as an alternative raw material suitable for biodiesel production. In this study, coconut waste is used to produce biodiesel using methanol and KOH. The oil content in coconut waste varies around 24 wt%. The highest yield, 97 % was achieved at 65 oC and 2.0 wt % catalysts loading within 3 hr by mixing raw material and methanol.